2004
DOI: 10.1111/j.1442-2042.2004.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Portless endoscopic radical nephrectomy via a single minimum incision in 80 patients

Abstract: Aim : To assess the feasibility of our portless endoscopic radical nephrectomy via a single minimum incision, which narrowly permitted extraction of the specimen in the initial 80 patients. Methods : Radical nephrectomy was carried out extraperitoneally in patients with T1-3aN0M0 renal tumors using an endoscope through a single minimum incision without trocar ports and gas. All the instruments used were reusable.Results : The average length of incision, operative time and estimated blood loss were 6.6 cm (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 15 publications
4
65
0
Order By: Relevance
“…Operative time and blood loss are similar to those in open surgery and complications including blood transfusion are very rare 17 . Postoperative data, days to oral feeding and days to walking are reported to be equal or sooner compared with LRN 17 and surgical site infection is extreamly rare despite the lack of use of prophylactic antibacterial agents 46 . These findings hold true even in ESRD patients.…”
Section: Minimum Incision Endoscopic Surgery Mies For Rcc ; Gasless mentioning
confidence: 68%
See 3 more Smart Citations
“…Operative time and blood loss are similar to those in open surgery and complications including blood transfusion are very rare 17 . Postoperative data, days to oral feeding and days to walking are reported to be equal or sooner compared with LRN 17 and surgical site infection is extreamly rare despite the lack of use of prophylactic antibacterial agents 46 . These findings hold true even in ESRD patients.…”
Section: Minimum Incision Endoscopic Surgery Mies For Rcc ; Gasless mentioning
confidence: 68%
“…Bleeding and operation time were comparable to LRN, as shown in Table.2. We already reported that this operation has minimal invasiveness similar to that of LRN 17 and an oncological outcome similar to that of open surgery 22 . Operative time and blood loss are similar to those in open surgery and complications including blood transfusion are very rare 17 .…”
Section: Minimum Incision Endoscopic Surgery Mies For Rcc ; Gasless mentioning
confidence: 99%
See 2 more Smart Citations
“…The patient underwent minimum incision endoscopic radical nephrectomy, which is also referred to as the portless endoscopic urological surgery, 6 via a right flank incision. Gross examination of the resected kidney weighing 1050g revealed multifocal tumors sized at 0.2-1.5 cm in the wall of several cysts and a gray-white tumor without pseudocapsule, measuring 2.0 cm ¥ 2.0 cm in the renal medulla (Fig.…”
Section: Case Reportmentioning
confidence: 99%